Metode Lean Six Sigma sebagai Strategi untuk Meningkatkan Kualitas Pelayanan dengan Meminimalkan Pemborosan dalam Pengadaan Bumbu Dapur pada Distributor X - Indriana Sari Soleha; Dedi Rohendi; Hanissa Okitasari (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
Increasing business competition requires companies to consistently improve quality and operational efficiency. This study aims to identify and reduce non-value added activities in the procurement process at Distributor X, a company engaged in the distribution of instant cooking spices. Common issues include expired goods (49.05%), damaged packaging (18.78%), and product mismatches (32.17%). The Lean Six Sigma approach with the DMAIC (Define, Measure, Analyze, Improve, Control) method is used to address these problems. Measurement results show an average DPMO value of 10,076.58 and a sigma level of 3.82, which are still far below the Six Sigma quality standard. Improvement proposals include the implementation of barcode/RFID systems, FIFO inventory management, higher-quality packaging materials, and the use of unique product codes. In the Control phase, monitoring is carried out through an ERP system and the establishment of structured SOPs to support distribution oversight. This approach demonstrates potential in reducing defect rates and improving the overall quality of the procurement process.